Legal Protection of Female Workers’ Leave Rights in Employment Practices in West Aceh Regency - Munawwarah Munawwarah; Teuku Saiful; Suhaimi Suhaimi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Female workers’ leave rights constitute normative rights protected under Article 79 of Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning Job Creation, as a form of legal protection for workers’ health and welfare. However, in practice within West Aceh Regency, the implementation of these rights still encounters several obstacles, including administrative requirements, managerial approval, and operational limitations within companies. This situation reflects a discrepancy between legal provisions and their practical implementation in the workplace. This study aims to examine the legal validity of female workers’ leave rights in employment contracts, the implementation of leave entitlements, and the forms of legal protection afforded to female workers in West Aceh Regency. The research employs an empirical juridical method with a qualitative approach through interviews and library research. The findings indicate that female workers’ leave rights possess a strong legal foundation and have been incorporated into employment agreements, thereby creating binding legal obligations for both parties. Nevertheless, the implementation of these rights has not been fully effective due to administrative barriers, managerial considerations, and limited workforce availability. Legal protection is provided through statutory regulations, employment contracts, and supervision by relevant authorities. Therefore, stronger oversight by the Department of Manpower, as well as greater consistency from companies in implementing leave provisions for female workers, is necessary to ensure effective legal protection.